Implementasi Manajemen Kurikulum Merdeka Belajar Dalam Menciptakan Profil Pelajar Pancasila di SMA Negeri 2 Muara Wahau - Septiani, Retno; Satriah, Satriah; Munfiatik, Siti (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
This research aims to explain the implementation of the Merdeka Belajar curriculum management in creating Pancasila Student profiles, identify obstacles in the implementation of the Merdeka Belajar curriculum management, and explore the efforts made to overcome challenges in the implementation of the Merdeka Belajar curriculum management at SMA Negeri 2 Muara Wahau. This research uses a qualitative approach with the type of field research, which was carried out at SMA Negeri 2 Muara Wahau. The research informants consisted of the school principal, deputy principal for curriculum, and driving teachers. The data collection techniques used included observation, interviews and documentation, which were analyzed descriptively qualitatively based on the Miles and Huberman data analysis model. The results of the research show that the implementation of the Merdeka Belajar curriculum management at SMA Negeri 2 Muara Wahau has gone well, referring to the management function POAC (Planning, Organizing, Actuating, Controlling), although there are obstacles related to understanding the concepts and objectives of the Merdeka Belajar curriculum which are still limited in among teachers, students and parents. Another obstacle is related to teachers' difficulties in determining appropriate learning methods. The proposed solution to overcome these obstacles is to involve all stakeholders in offline and online training, which aims to increase teachers' understanding of the core Merdeka Belajar curriculum and improve teachers' abilities in implementing innovative teaching methods. Apart from that, outreach to students' parents was also carried out to introduce the Merdeka Belajar curriculum in more depth.